Short-Term Memory in the Production Phase of Sight Translation - Pedersen, Emile Sand; Dam, Helle V. (HERMES - Journal of Language and Communication in Business, 2014)
This article reports on an empirical study on short-term memory in sight translation. The aim of the study was to test the hypothesis that sight translation requires the use of short-term memory during target-text production, as suggested by previous research. The hypothesis was tested on the basis of an experiment involving sight translation from Spanish into Danish and subsequent interviews with the translators. The data – the Spanish source text, seven sight translations into Danish, and the post-interviews – were analysed using both quantitative and qualitative methods, and the results of the study confirmed the hypothesis. In fact, the (quantitative) analyses of the sight-translated texts indicated that the subjects needed their short-term memory extensively during target-text production. However, the (qualitative) analyses of the interviews showed that the subjects had little awareness of this need.